Decondensation behavior of DNA chains induced by multivalent cations at high salt concentrations： Molecular dynamics simulations and experiments - 蒋杨伟 冉诗勇 何林李 王向红 章林溪 (Chinese physics B, 2015)
Using molecular dynamics simulations and atomic force microscopy （AFM）, we study the decondensation process of DNA chains induced by multivalent cations at high salt concentrations in the presence of short cationic chains in solutions. The typical simulation conformations of DNA chains with varying salt concentrations for multivalent cations imply that the concentration of salt cations and the valence of multivalent cations have a strong influence on the process of DNA decondensation. The DNA chains are condensed in the absence of salt or at low salt concentrations, and the compacted conformations of DNA chains become loose when a number of cations and anions are added into the solution. It is explicitly demonstrated that cations can overcompensate the bare charge of the DNA chains and weaken the attraction interactions between the DNA chains and short cationic chains at high salt concentrations. The condensation-decondensation transi- tions of DNA are also experimentally observed in mixing spermidine with X-phage DNA at different concentrations of NaCl/MgCl2 solutions.